Pemberdayaan Usaha Binatu Lokasi Terdampak eks-lokalisasi Daerah Morokrembangan Surabaya - Setiyawan, Radius; Jayadi, Mahsun (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
After the closing of localization on December 12, 2012 by the Mayor of Surabaya, there are several stand-by laundry businesses run by former WTS (Women Tuna Susila). The business has been running for 2 years but there are some significant obstacles so the business still has not revealed significant results. Some of the obstacles faced are: Financial management that is still not regular so that is still often mixed between personal money with business money, promotion model is still conventional and some other problems. Based on the above problem, the solutions offered are as follows: (a) the addition of production equipment so as to speed up the drying process and minimize dependence on sunlight; (b) train effective and controlled bookkeeping; (c) train the proper Laundry chemistry; (d) create a creative and technology-based promotional model. From the results of the above empowerment, it proved to be an improvement of management and able to increase the productivity of the business.